Role of microRNAs in schistosomes and schistosomiasis - Zhu, Lihui; Liu, Jinming; Cheng, Guofeng (Frontiers in Cellular and Infection Microbiology, 2014)
Schistosomes, a class of parasitic trematode worms, cause schistosomiasis. Accumulating evidence suggests that microRNAs (miRNAs)—small, non-coding RNAs that are known to play critical regulatory roles in many organisms—may be involved in schistosome development and sexual maturation, as well as the pathogenesis of schistosomiasis. Schistosoma miRNAs, such as Bantam and miR-10, may be involved in the pathological processes of schistosomiasis, and recent studies suggest that schistosome-specific miRNAs (e.g., Bantam, miR-3479-3p) in the bloodstream of a final host could be used as biomarkers for schistosomiasis diagnosis. Furthermore, aberrant miRNAs, such as miR-223 and miR-454, can be produced by a host in response to schistosome infection, and these miRNAs may contribute to the pathogenesis of schistosomiasis-associated liver injury. Here, we summarize recent progress evaluating the relationship between schistosome miRNAs and schistosomiasis and discuss how these miRNAs can mediate the pathogenesis of schistosomiasis and be used as biomarkers for schistosomiasis diagnosis.